Autophagosomes cooperate in the degradation of intracellular C‐terminal fragments of the amyloid precursor protein via the MVB/lysosomal pathway. Issue 6 (2nd March 2017) - González, Alexis E.; Muñoz, Vanessa C.; Cavieres, Viviana A.; Bustamante, Hianara A.; Cornejo, Víctor‐Hugo; Januário, Yunan C.; González, Ibeth; Hetz, Claudio; da Silva, Luis L.; Rojas‐Fernández, Alejandro; Hay, Ronald T.; Mardones, Gonzalo A.; et al.
ABSTRACT: Brain regions affected by Alzheimer disease (AD) display well‐recognized early neuropathologic features in the endolysosomal and autophagy systems of neurons, including enlargement of endosomal compartments, progressive accumulation of autophagic vacuoles, and lysosomal dysfunction. Although the primary causes of these disturbances are still under investigation, a growing body of evidence suggests that the amyloid precursor protein (APP) intracellular C‐terminal fragment β (C99), generated by cleavage of APP by β‐site APP cleaving enzyme 1 (BACE‐1), is the primary cause of the endosome enlargement in AD and the earliest initiator of synaptic plasticity and long‐term memory impairment. The aim of the present study was to evaluate the possible relationship between the endolysosomal degradation pathway and autophagy on the proteolytic processing and turnover of C99. We found that pharmacologic treatments that either inhibit autophagosome formation or block the fusion of autophagosomes to endolysosomal compartments caused an increase in C99 levels. We also found that inhibition of autophagosome formation by depletion of Atg5 led to higher levels of C99 and to its massive accumulation in the lumen of enlarged perinuclear, lysosomal‐associated membrane protein 1 (LAMP1)‐positive organelles. In contrast, activation of autophagosome formation, either by starvation or by inhibition of the mammalian target of rapamycin, enhanced lysosomal clearance of C99. Altogether, our results indicate that autophagosomes are key organelles to help avoid C99 accumulation preventing its deleterious effects.—González, A. E., Muñoz, V. C., Cavieres, V. A., Bustamante, H. A., Cornejo, V.‐H., Januário, Y. C., González, I., Hetz, C., da Silva, L. L., Rojas‐Fernández, A., Hay, R. T., Mardones, G. A., Burgos, P. V. Autophagosomes cooperate in the degradation of intracellular C‐terminal fragments of the amyloid precursor protein via the MVB/lysosomal pathway. FASEB J. 31, 2446–2459 (2017). www.fasebj.org